Analisis dan Pengembangan Sistem Monitoring Stok, Penjualan Serta Pembelian BBM (Bahan Bakar Minyak) : (Studi Kasus pada SPBU 85.988.02 Wadio) - Gunawan Prayitno; Novita Paraga; Usman Arfan (STMIK Pesat Nabire, 2024)
The oil fuel stock monitoring system (BBM) is becoming crucial to the management of valuable energy assets. The aim of the author is to conduct an effective system analysis and development to monitor BBM stocks. The research uses prototyping methods, which include the following steps: identification of initial needs, initial prototype making, evaluation and feedback, improvement and development, final implementation, and final evaluation. An easy-to-understand user interface design and an efficient database structure are important components of system design. Web-based software development is part of the system implementation. The testing process is carried out to ensure the performance, reliability, and security of the system. The system is regularlyined to remain functional and relevant. It is expected that the results of this practice will make a significant contribution in improving the efficiency and accuracy of monitoring BBM stocks. Moreover, these results will provide the basis for similar system development in the future.